Aspek Finansial Pengembangan KomoditasPisang Hias (Heliconiasp.) Di Sekar Bumi Tropical Farm & Florist Desa Kerta, Kecamatan Payangan, Kabupaten Gianyar - KOMANG TRIYULIANTI; MADE SUDARMA; RATNA KOMALA DEWI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2015)
Abstract Financial AspectOrnamental Banana(Heliconia sp.) InSekarBumiTropical Farm& Florist at KertaVillage, Payangan District,Gianyar Regency Heliconia flowernewlydevelopedcommodity, in 2011it’sproductionamounted to936 426stalksor25% of allcommoditiesof cut flowersinBali province. The purposeof this researchincludesthe prospectsof Heliconia flowerin termsoffinancial aspect, marketingaspectandconstraintsencountered in the developmentof commodityinSekarBumi atKertaVillage, Payangan District,Gianyar Regency. The results showedHeliconiaflower businessinSekarBumiFarmis feasiblebased on the financialaspect.Thisagribusinessinvestmenthasto fill several criteria, among others, the NetB/C>1isRp 1.48, NPV>0isRP153.332.226,73,IRR>discount factorof 18%, which is22.38% andpaybackperiodless than productive of this plant(10 years) is5,32years. Sensitivity analysisshowedthat development of Heliconia is no longer feasible to conduct if the increase cost of labor is more than 3% or the revenue falls below 14%. The problemsfaced in this business, consist oftwofactors:internal and external factors. Internal factorsincludelack of capitalinvestmentandlimited number of varietiesof the plants. While, the external factoriscompetitionwithimported productsandfrom outside region.It is suggested that SekarBumiFarmmanagerstoincreaseHeliconiaflowertypesandto expandthe marketingnetwork. Keywords: Heliconia, InvestmentCriteriaAnalysis, Prospects, FinancialAspect, AspectMarketing.